Benzonitrile-functionalized non-fullerene acceptors for organic solar cells with low non-radiative loss. Issue 45 (9th November 2022) - Sun, Cheng-Zhe; Lai, Xue; Rehman, Tahir; Lai, Hanjian; Ke, Chunxian; Shen, Xiangyu; Zhu, Yulin; Tian, Leilei; He, Feng
Abstract : Three non-fullerene acceptors with benzonitrile groups were synthesized, which could reduce the non-radiative recombination energy loss and enhance the efficiency in organic solar devices. Abstract : The photovoltaic performance of organic solar cells (OSC) has been compromised by the large energy losses. Non-radiative recombination energy losses (Δ E 3 ) are the major factor in the energy loss but can be modulated by rational molecular design. Herein, three new non-fullerene acceptors (NFAs), BTIC-4CN, BTIC-γ-2CN, and BTIC-γ-4CN were synthesized by the substitution of benzonitrile or benzodinitrile groups on the end groups. The photovoltaic performances were investigated by blending each acceptor with the complementary D18 donor polymer. Among them, BTIC-γ-2CN based devices exhibited the best PCE of 16.03% with a low non-radiative recombination energy loss of 0.191 eV. Ternary devices with NFAs of BTIC-γ-2CN and Y6 achieve an impressive high PCE of 17.61%. This good photovoltaic performance is attributed to the improved light absorption ability, optimized film morphology, and reduced non-radiative recombination loss. This work reveals the significance of substituting aryl nitrile groups on the end groups to simultaneously improve the photovoltaic performance with low non-radiative recombination losses.